PERANCANGAN E-CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS CROSS PLATFORM MEMANFAATKAN WEB SERVICE PADA PERUSAHAAN SOFTWARE HOUSE - Nuraminudin Nuraminudin; Ema Utami; Hanif Al Fatta (Informasi Interaktif, 2018)
Software house company is a business unit whose outline is developing or creating software to provide solutions for clients or customers, be it from government, companies, organizations, or individuals. The key to the success of software house companies lies in the relationship with clients. Problems arise when companies implement remote work and communication systems between clients and companies are not well established during project execution resulting in low client satisfaction. In order for communication between client and company to be well established, Electronic Collaborative CRM system design developed in cross platform with web service as bridge and its integration media is proposed, so that client and company employees can use this system anytime anywhere and with different platforms. The output of this research is a system design that contains Unified Modeling Language (UML) diagrams, data design in the form of Entity Relational Diagram (ERD) and User Interface design and prototype designed to run on various platforms. The designed prototype is acceptable to both the client and the employee after all aspects tested using a Likert-scale questionnaire get a "good" or "excellent" classification score (above 60%). So that proves Collaborative CRM felt important and needed by clients and employees. Keyword: software house, electronic collaborative CRM, cross platform, web service